Challenges in Retaining Skilled Workforce in Remote Mining Areas of Mongolia - Narivo Harinandrasana Anjatiana Merisoa; Shahabuddin Esmati; Ahmed Djoumoi; Randriatsilanimanga Sendra Symphrose (The Nexus Journal of Education, Management, and Entrepreneurship, 2026)
This study examines the persistent challenge of retaining skilled workers in remote mining areas of Mongolia, aiming to identify the individual, organizational, and structural factors that influence workforce retention in geographically isolated mining regions. A qualitative case study design was employed, drawing on semi-structured interviews, focus group discussions, and document analysis conducted at major mining sites, including Oyu Tolgoi and Tavan Tolgoi. Participants include current and former mining employees, human resource managers, vocational educators, and community members. Data were analyzed thematically using Braun and Clarke’s six-phase framework, with NVivo software to support systematic coding and interpretation. The findings reveal that workforce retention is shaped by a complex interplay of factors, including family dislocation, harsh working conditions, limited career advancement opportunities, gender-based barriers, and a misalignment between vocational training and industry needs. Social isolation, inflexible human resource policies, and inadequate living infrastructure further contribute to high attrition rates, while salary incentives alone prove insufficient for long-term retention. By centering workers’ lived experiences and integrating perspectives from industry, education, and community stakeholders, this study provides a context-specific and holistic understanding of workforce retention challenges in Mongolia’s mining sector, offering practical insights for policy reform and human resource strategies in remote, resource-dependent economies.